Hierarchical Nanogold Labels to Improve the Sensitivity of Lateral Flow Immunoassay - Serebrennikova, Kseniya; Samsonova, Jeanne; Osipov, Alexander (Nano-Micro Letters, 2017)
Lateral flow immunoassay (LFIA) is a widely used express method and offers advantages such as a short analysis time, simplicity of testing and result evaluation. However, an LFIA based on gold nanospheres lacks the desired sensitivity, thereby limiting its wide applications. In this study, spherical nanogold labels along with new types of nanogold labels such as gold nanopopcorns and nanostars were prepared, characterized, and applied for LFIA of model protein antigen procalcitonin. It was found that the label with a structure close to spherical provided more uniform distribution of specific antibodies on its surface, indicative of its suitability for this type of analysis. LFIA using gold nanopopcorns as a label allowed procalcitonin detection over a linear range of 0.5–10 ng mL−1 with the limit of detection of 0.1 ng mL−1, which was fivefold higher than the sensitivity of the assay with gold nanospheres. Another approach to improve the sensitivity of the assay included the silver enhancement method, which was used to compare the amplification of LFIA for procalcitonin detection. The sensitivity of procalcitonin determination by this method was 10 times better the sensitivity of the conventional LFIA with gold nanosphere as a label. The proposed approach of LFIA based on gold nanopopcorns improved the detection sensitivity without additional steps and prevented the increased consumption of specific reagents (antibodies). Highlights: 1 New types of nanogold labels were evaluated for their improved sensitivity in procalcitonin lateral flow immunoassay (LFIA). 2 Gold nanostars and nanopopcorns were applied as a label in a sandwich-format LFIA. 3 The use of gold nanopopcorns as a label demonstrated a fivefold increase in sensitivity compared to that associated with the conventional LFIA based on 20-nm gold nanospheres.